EFFICACY AND SAFETY OF PROLONGED TREATMENT WITH CYCLOSPORINE IN CHILDREN WITH FOCAL SEGMENTAL GLOMERULOSCLEROSIS - O.V. Komarova; M.V. Matveeva; A.N. Tsygin; L.V. Leonova; A.G. Timofeeva ("Paediatrician" Publishers LLC, 2010)
The article analyzes results of successful prolonged treatment of children with focal segmental glomerulosclerosis (FSGS). Treatment with cyclosporine (median dose 4-5 mg/kg of body weight) combined with prednisolone (1-1.5 mg/kg/48 hours) was performed in 34 patients 1.5-16 years old with FSGS. Pulse-treatment with methylprednisolone (30 mg/kg every other day, 3-6 injections) was performed in 21 patients for the purpose of remission induction. In 6 month of treatment with cyclosporine, total clinical and laboratory remission of corticosteroid-resistant nephrotic syndrome (CRNS) was detected in 12 (35%) patients, partial one - in 9 (26%) patients, remaining CRNS - in 13 (38%) of children. In 12 months of treatment total remission of CRNS was detected in 18 (53%) children, partial one - in 7 (21%) children, unefficient treatment - in 7 (21%) patients. Dose of prednisolone was decreased to minimal supporting level in 68% of children, and in 32% of patients corticosteroids were canceled. Thus, treatment with cyclosporine was effective in most children with SRNS and FSGS. Prolonged administration of cyclosporine up to 2 years and longer can be performed if regular control of kidney function is provided and symptoms of nephrotoxic action of this drug is absent (according to results of repeated biopsy).Key words: children, focal segmental glomerulosclerosis, cyclosporine, methylprednisolone.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):155-159)